2023
DOI: 10.22271/j.ento.2023.v11.i1b.9144
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of ectoparasite of dogs in the State of Tripura

Abstract: A cross-sectional study was conducted between November 2021 to October 2022, to determine the prevalence of ectoparasites in dogs of different sex, breed and age groups in Tripura. The objectives of the study were to determine the prevalence of ectoparasites, determine associated risk factors and identify the most important ectoparasites species of dogs in four districts of Tripura. A total of 528 dogs were screened for ectoparasites and were identified using standard taxonomic keys.Of 528 dogs, 69.69% (368/52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…In the current study we found that stray dogs had the highest breed of infestation rate compared to other breeds (38.4%) this finding agreed with (Sarkar et al, 2023) who found stray dogs harboring the highest infested dogs (79.80%) in Tripura. This may be due to increased changes of infestation among fee dogs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study we found that stray dogs had the highest breed of infestation rate compared to other breeds (38.4%) this finding agreed with (Sarkar et al, 2023) who found stray dogs harboring the highest infested dogs (79.80%) in Tripura. This may be due to increased changes of infestation among fee dogs.…”
Section: Discussionsupporting
confidence: 91%
“…It was noted in the current study that dogs of 7 months to 1 year of age had a higher ectoparasite infestation (15.86%) than other ages. This finding was similar to (Sarkar et al, 2023), who declared that the highest infestation rate was noted in dogs at the age of 6 months to 1 year (79.66%), while (Abdulkareem et al, 2019;Shoorijeh et al, 2008) who mentioned that the prevalence of ectoparasite infestation was the highest in dogs aged from 1 to 6 months (9.4%) in Iran and Nigeria; respectively. The differences recorded in the present study may be attributed to the difference in dog's breeds or environmental factors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, this species has been reported from the island of Sulawesi, an Indonesian island considered to lie within the Australasian faunal region (Durden et al 2008), and the southernmost geographic record for A. varanense. Currently, A. varanense is known from the following countries: Bangladesh (Burridge 2001), Cambodia (Petney et al 2019), China (Chen et al 2010;Zhang et al 2018), India (Patra et al 2016), Indonesia (Durden et al 2008;Supriyono et al 2019), Laos (Petney & Keirans 1996;Vongphayloth et al 2016), Malaysia (Kho et al 2015;Xian 2018), Myanmar (Supino 1897;Frazier & Keirans, 1990), Nepal (Pun et al 2018), Papua New Guinea (Kenny et al 2004), Singapore (Burridge 2001;Kwak 2018), Sri Lanka (Fernando & Kulasena-Fernando 2012;Liyanaarachchi et al 2015), Taiwan (Robbins 1996), Thailand (Tanskul et al 1983;Sumrandee et al 2015), and Vietnam (Huynh et al 2021). Furthermore, due to its wide geographic range in South and Southeast Asia, we expect that A. varanense will eventually be reported from such poorly collected states as Bhutan, and it likely occurs on several small islands near the Southeast Asian mainland, such as those in the Andaman and Nicobar archipelagos.…”
Section: Geographic Distribution Of a Varanensementioning
confidence: 99%